Testing collocational knowledge of Yemeni EFL university students at Universiti Utara Malaysia - Banboua, Nabil Mohammed S. (2016)
It is commonly acknowledged that collocations play an important role in the field of ESL/EFL acquisition.Previous seminal studies have reported students‟ development of collocational knowledge and use of collocations regardless the difficulties students may encounter in learning collocations, specifically, Arab students. The present study focuses on students‟ collocational knowledge, particularly, Yemeni EFL university students who were attending an Intensive English Course (IEC) at UUM/Malaysia.The data was collected from only five Yemeni students (two postgraduate and three undergraduate).Those were the only Yemeni students who were attending the IEC. All of the participants were male students. The participants' collocational knowledge was tested by a Multiple-choice Collocational Test (MCT). The results of the statistical analysis revealed that participants' collocational knowledge was less than the expected. Moreover, the results concluded that students‟ lack of knowledge of collocations was due to the fact that collocations were not of a focus in teaching English as a foreign language in schools. The study also ended up with recommendations for future research.